ANALISIS EFEKTIFITAS SISTEM PERFORMANCE APPRAISAL PADA PT PATRA BADAK ARUN SOLUSI - Hanum Faza; Mukaram Mukaram (Ebiz Prima Nusa, 2023)
The effectiveness of the performance appraisal system is a unit consisting of interrelated elements with goals as a measuring tool to assess the properties of work, individual characteristics, and the final result of how productive the individual is in handling his work, which is then used to achieve optimal results, according to organizational goals. In measuring the effectiveness of the performance appraisal system, five dimensions are used, namely relevance, sensitivity, reliability, practicality, and acceptability. The purpose of this study was to determine the effectiveness of the performance appraisal system of PT Patra Badak Arun Solusi. Sampling amounted to 102 people using incidental sampling techniques. The data collection technique was by distributing a questionnaire containing 10 statements distributed to employees as a measure of the effectiveness of the performance appraisal system at PT Patra Badak Arun Solusi. After that, the data was processed using the SPSS version 22 application, which was then analyzed. Descriptive analysis shows the effectiveness of the performance appraisal system for employees at PT Patra Badak Arun Solusi is effective. The mean is 3.89